"Meaningful use" provides a meaningful opportunity. Issue 4 (25th October 2013) - Rabius, Vance; Karam‐Hage, Maher; Blalock, Janice A.; Cinciripini, Paul M.
<x xml:space="preserve">Abstract</x> A model is described for meeting the mandate that includes implementation of a comprehensive smoking (tobacco) cessation program for cancer patients as an alternative to the minimal intervention approach. The importance of an institution‐wide, automated system to identify and refer tobacco users to treatment is discussed within the context of implementing the meaningful use regulations for electronic health records.